Eimeria macusaniensis associated lesions in neonate alpacas dying from enterotoxemia - Rosadio R. (2010)
This study was partially supported by San Marcos University, CONCYTEC, INCAGRO, FINCyT and the CONOPA Research Institute. Special Thanks to J. C. Wheeler for assistance writing the manuscript and to the many Veterinarians and alpaca breeders who collaborated so effectively in collecting the samples reported in this study.